Republic of Togo : Urban and Peri-Urban Development and Policy Note - Amankwah-Ayeh, Kwabena (World Bank, Washington, DC, 2013)
This review concludes that for Togo's urban and peri-urban areas to sustainably grow, issues of urban governance and development need to be approached in a comprehensive manner, driven by well -guided policies developed in partnership with the people to support Sub-National Government Authorities and Entities(SGAs) in carrying out their functions efficiently. To meet evolving challenges of urbanization and decentralization, the Government of Togo (GoT) must rationalize the roles of various levels of government and agencies and limit their numbers to limit duplication, strengthen the capacities of relevant sector institutions and coordinate institutional actions and investments. It is further recommended that GoT must (i) clarify the roles and functions of national, prefectural, and local governments while ensuring that coordination functions between them work well; (ii) separate urban policy and regulatory functions from implementation of urban projects by allocating implementation responsibilities to private operators or qualified state agencies under performance-based arrangements; (iii) ensure proper allocation of taxing responsibilities, develop and implement transfer of financial resources from the central government to the local governments on a transparent basis supported by simple and precise criteria; and (iv) strengthen the central government s role in policy, regulatory, coordination, oversight and supervision. Contractualization of relationships between different tiers of government and benchmarking of performance must be prominent among the guiding principles that should govern the delivery of responsibilities of GoT, SGAs and their agencies. Finally, this necessary, first step stock-taking review of Togo s urban and peri-urban sector has revealed knowledge & data gaps that need to be filled through further analysis and studies on (a) infrastructure services provision needs as well as capacity to implement, operate and maintain them, (b) improving the functioning of the urban land market and shelter-related issues, (c) strengthening municipal financing, (d) developing city and local economic development strategies (CDS & LED), and (e) socio-economic and technical approaches to financing of slum upgrading.